Assessment the thermoforming effect on the physical and mechanical properties of different thermoplastic orthodontic retainers: An in vitro study - Doaa N. Hamid; Mustafa M. AL-Khatieeb (Journal of Orthodontic Science)
OBJECTIVES: As patients are instructed to wear thermoplastic retainers for the rest of their lives, the durability of the materials is a critical factor in evaluating whether the expense is justified. This study examined the physical and mechanical properties of three different thermoplastic retainer materials before and after thermoforming (BT and AT). MATERIALS AND METHODS: Clear Advantage Series I, Clear Advantage Series II, and Leone types were used, with each material having a thickness of 1 mm. The materials’ tensile force, hardness, and water absorption tests have been measured for 90 thermoformed and 90 non-thermoformed specimens (30 specimens from each material). RESULTS: The tensile force, hardness, and water absorption values of all the materials differed significantly (P ≤ 0.05) BT. Additionally, the majority of the materials showed significant differences in water absorption, hardness, and tensile force (P ≤ 0.05) AT, except the Leone materials, and Clear Advantage Series I did not significantly differ in the case of hardness value. All studied materials showed an increase in hardness and water absorption AT (P ≤ 0.05). At the same time, all of the studied materials showed a significant decrease in tensile force after thermoforming. CONCLUSION: Thermoforming increases the material’s water absorption while decreasing its stiffness, affecting its mechanical and physical properties. Clear Advantage Series II (PP) stood out with superior flexibility, wear resistance, and minimal water absorption compared to other materials, highlighting its durability and superiority.